Comparative study of biochemical characteristics, external and internal structure of roots in natural and cultivated Scutellaria baicalensis Georgi. - Battseren, Tsambaa; Batzaya, Gachmaa; Tserenkhand, Gundsambuu; Azzaya, Jukov (Mongolian Journal of Botany, 2023)
This research aims to develop the method and standards of primary raw materials between cultivated and natural plants thereto conservative and protect the resource of the natural plants, massive cultivate for usage, increase the resource of primary raw material, moreover enhance the opportunity to produce the home products. S. baicalensis is widely distributed in the Eastern provinces of Mongolia and grows on low mountainsides, valleys, and grassy slopes at an altitude of 730-1150 m. Root biomass outcomes were different at each vegetation community, ranging between 49.2-64 g/м2, average root biomass was 62.8 g/м2, the individual plant was 2-6 at each plot, average 4, root dry biomass was ranged between 8.2 – 20.1 g and average were 15.7 g respectively. The root biomass drying rate of Scutellaria baicalensis was 60,6%. Therefore, the root biomass outcome of cultivated samples was 122.4 g/м2, the individual plant was 9 at each plot, root dry biomass was 13.6g, and the drying rate of cultivated root biomass was 64.6%. Results of the root external comparison between natural and cultivated samples were identified that the reddish epidermis of the root of natural samples were 2-3 times thicker than cultivated samples’, moreover internal of the root was deep yellow, reddish, fluffy, not dense, root diameter was ranged between 0.6-3 cm, averagely 1.5±0.7 cm. Whereas the root epidermis of the cultivated sample was thin, the internal root deep yellowish, root diameter was ranged from 0.6-2 cm, average of 1.2±0.5 cm, but the taste and smell of the root was not pungent smell and all root samples were tasted bitter. The secondary covering tissue (peridermis) of S.baicalensis root growing under natural conditions is disrupted and largely part is occupied by the xylem parenchyma and vessels. For this reason, the central part of the root is formed by a cavity, which indicates that it grows in relatively dry conditions. However, periderms of S.baicalensis root growing under cultivated conditions are composed of evenly thickened cell walls and largely cambium. Moreover, Xylem cells and vessels are equal, which can determine that it develops normally. According to the pharmacopeia’s standard method, the total alkaloid content, moisture content, and ash content of the root’s biochemical samples were determined. Biochemical research has determined that the root total alkaloid, moisture, and ash content of S. baicalensis differ statistically (p<0.05) depending on the geographical location. There are no statistical differences (p>0.05) between the natural and cultivated conditions of Scutellaria baicalensis, although both samples’ total alkaloid and moisture contents (0.3%, 0.75-1.8%) fit the standards for medicinal raw materials. In natural samples, there was a tendency to be higher. However, compared to samples grown under cultivated conditions, the ash concentration in the natural samples was significantly different (p<0.05) or higher. Байгалийн гүүнхөх (Scutellaria baicalensis Georgi)-ийн үндэсний гарц, гадаад, дотоод бүтэц, биохимийн харьцуулсан судалгаа Хураангуй: Энэхүү судалгаа нь байгалийн ургамлын нөөцийг хамгаалах, тарималжуулан ашиглаж үйлдвэрлэлийн нөөцийг нэмэгдүүлэн, дотоодод нэмүү өртөг шингэсэн бүтээгдэхүүн үйлдвэрлэх боломжийг бүрдүүлэхэд байгалийн болон таримал ургамлын түүхий эдийг өөр хооронд нь ялгах арга аргачлал, стандартыг боловсруулах зорилготой. Байгалийн гүүнхөх нь Монголын Дорнод хэсэгт уулын хажуу, нам уул, цав толгодын дунд д.т.д. 730-1150 м өндөрт ургаж, үндэсний гарц 1м2 талбайд 62.8 гр/м2 , бодгалийн тоо дунджаар 4, үндэсний хуурай жин дунджаар 15.7гр, хаталтын хувь 60.6%-тай. Таримал хэлбэрт үндэсний гарц 122.4 гр/м2, бодгалийн тоо нэгж талбайд дунджаар 9, үндэсний хуурай жин дунджаар 13.6 гр байна. Хаталтын хувь нь 64.6%-тай байна. Байгалийн гүүнхөхийн үндэсний гадаад бүтцийн харьцуулсан судалгаагаар G1 буюу үржлийн залуу насны бодгалийн үндэсний хүрэн хальс байгалийн дээжинд 2-3 давхар зузаан, голч хэсэг бараан, хөвсгөр хуураймтгай, нягт биш, үндэсний диаметр 0.6-3см дунджаар 1.5±0.7 см. Харин таримал хэлбэрт үндэсний хүрэн хальс нимгэн, голч нь цайвар, хөвсгөр хуурамтгай биш, нягт, үндэсний диаметр 0.6-2см дунджаар 1.2±0.5 см байсан бол үнэр, амтын хувьд 2 хэлбэрт үндэс содон үнэргүй, гашуун амттай байв. Байгалийн үндэсний перидермийн давхраа зузаарсан, үндэсний ихэнх хэсгийг модожсон паренхим, гуурсууд томорч хөндий зай үүсгэж байгаагаас харахад, 3 настай харьцангуйгаар хуурайсаг нөхцөлд ургасан болохыг илэрхийлж байна. Харин таримал Байгаль гүүнхөхийн үндэсний анхдагч холтосны давхраа эвдэрч перидермийн давхраа үүсгэсэн, үндэсний төв хэсэгт байрлах модлогийн эсүүд, гуурс жигд хөгжсөн ньгуравдагч бүтэц рүү шилжиж байгааг харуулж байна Байгалийн гүүнхөхийн үндэсний нийлбэр алкалоид, чийг болон үнслэгийн агууламж газарзүйн байршлаас хамаарч статисикийн хувьд ялгаатай (p<0.05) байгааг тогтоосон. Нийлбэр алкалоид, чийгийн агууламж нь эмийн түүхий эдийн стандартыг (0.3%, 0.75-1.8%) хангаж байсан ба байгаль болон таримал хэлбэр хооронд статистик ялгаа (p>0.05) харагдахгүй ч тоон утгаараа байгалийн дээжинд өндөр байх хандлага ажиглагдсан. Харин үнслэгийн агууламж нь байгалийн дээжинд өндөр агууламжтай (p<0.05) байв. Түлхүүр үгс: Байгалийн гүүнхөх, үндэсний гадаад, дотоод бүтэц, нийлбэр алкалоид